Pengaruh Pemberian Air Kelapa dan Kalium Iodat Terhadap Sifat Kimia Tanah dan Kandungan Yodium Dalam Biji Jagung Manis - Minarni Minarni; Sufardi Sufardi; Muyassir Muyassir (Jurnal Manajemen Sumberdaya Lahan, 2015)
Abstract: Role of Potassium Nutrient extremely vital in sweet corn farming .Potassium iodate compounds and coconut water is suspected to be the best alternative solution.his study aimed to observe the effect of dose Potassium iodate and coconut water on the growth and yield as well as the iodine content in sweet corn kernels (Zea mays L. Var. Saccharata).This study compiled a completely randomized design with three replications in a factorial .There are two factors studied , each dose of potassium iodate factor consisting of three levels , namely treatment: 0 , 60 , 90 kg ha-1 and dose factors coconut water treatment consists of three levels namely : 0 , 5500 and 11000 liters ha-1 . There is no interaction effect between the dose of potassium iodate and coconut water to soil pH, total soil N and K-dd. interaction effects occur between doses of potassium iodate and the iodine content of coconut water in the corn kernels and p available. provision of potassium iodate and coconut water can increase the iodine content in the seed corn of 2.58% when compared to the iodine content by providing 0 kg of potassium iodate and 0.36% coconut water. Abstrak: Peranan hara kalium sangat urgen dalam pertanian jagung manis. Senyawa kalium iodat dan air kelapa diduga dapat menjadi alternatif solusi terbaik. Penelitian yang bertujuan untuk mengamati pengaruh interaksi antara dosis kalium iodat dan air kelapa terhadap sifat kimia tanah, dan kandungan iodium dalam biji jagung (Zea mays L. Var. Saccharata) yang berlangsung dari bulan September sampai Desember 2013.  Penelitian ini menggunakan rancangan acak lengkap (RAL) pola faktorial dengan tiga ulangan.  Ada dua faktor yang diteliti yaitu faktor dosis kalium iodat dan air kelapa yang terdiri  atas tiga taraf kalium iodat  (0, 60, 90 kg ha-1) dan tiga taraf air kelapa (0, 5500, 11000 liter ha-1). Tidak ada efek interaksi antara dosis kalium iodat dan air kelapa terhadap pH tanah , N-total tanah dan K-dd. Terjadi efek interaksi antara dosis kalium iodat dan air kelapa terhadap kadar iodium dalam biji jagung dan P-tersedia. Pemberian kalium iodat dan air kelapa dapat meningkatkan kadar iodium dalam biji jagung 2,58 % bila dibandingkan dengan kadar  iodium dengan pemberian 0 kg-1 kalium iodat dan air kelapa sebesar 0,36 %